2022
DOI: 10.1002/jad.12067
|View full text |Cite
|
Sign up to set email alerts
|

Stability and changes in high school students' STEM career expectations: Variability based on STEM support and parent education

Abstract: Introduction Why do some students maintain their career expectations in STEM (science, technology, engineering, mathematics), whereas others change their expectations? Using situated expectancy‐value and social cognitive career theories, we sought to investigate the extent to which STEM support predicted changes in students' STEM career expectations during high school, and if these processes varied by whether the student had college educated or noncollege educated parents. Methods Using the nationally represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Documenting these increases contributes to motivation theory and calls in question the leaky STEM pipeline metaphor that assumes people who leave STEM do not return and that no one switches from non-STEM into STEM fields. The findings from this study and others (e.g., Hsieh & Simpkins, 2022;Starr, Carranza, & Simpkins, 2022) suggest that the pathways in and out of STEM are more fluid with some students moving toward STEM during high school. It also suggests that middle and high school are not too late to spark Asian and Latinx students' math motivational beliefs.…”
Section: Latinx and Asian Adolescents' Math Interest Utility Value An...supporting
confidence: 54%
“…Documenting these increases contributes to motivation theory and calls in question the leaky STEM pipeline metaphor that assumes people who leave STEM do not return and that no one switches from non-STEM into STEM fields. The findings from this study and others (e.g., Hsieh & Simpkins, 2022;Starr, Carranza, & Simpkins, 2022) suggest that the pathways in and out of STEM are more fluid with some students moving toward STEM during high school. It also suggests that middle and high school are not too late to spark Asian and Latinx students' math motivational beliefs.…”
Section: Latinx and Asian Adolescents' Math Interest Utility Value An...supporting
confidence: 54%
“…Primary school and preschool teachers in Türkiye and Romania suggested overcoming these difficulties, with parents' help, and this brings up the question for the potential of school-family partnerships as a formal support strategy for STEAM implementation at all education levels in all countries. It is worth considering that parents play an essential role in constructing children's professional aspirations and influencing their professional orientation [48,49]. Also, the results highlighted the issue of school partnerships with local or national institutions as being a key action for overcoming the difficulties related to the lack of proper teaching resources or the lack of STEM training, both in primary and preschool education [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…The apparent intention is to influence children's interests positively and help them find their path in the world, remaining resilient toward gender-based prejudice. However, intentions need to find a practical deployment, and there is still a pronounced need to organize more joint-up activities, such as involving children, parents, and the broader STEM community, including businesses and academia [49,50,58]. This will allow parents and children alike to discover the excitement and the practical implementations of STEAM learning [69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental expectation in uences STEM-related hopes and goals.Studies have shown that parental expectancy affects not only STEM-related hopes and goals, but also STEM career aspirations. Chen et al (2022) reported a signi cant relationship between both short-term and long-term parental expectations and STEM career aspirations Starr et al (2022). reported that parental support has a signi cant effect on a stable STEM career, while Yine Lv et al (2022) conveyed that parental support is a signi cant predictor of STEM career interest for both girls and boys among high school students.…”
mentioning
confidence: 99%